Analisis Dampak Penerbitan Sertifikat Laik Fungsi (SLF) Terhadap Nilai dan Kinerja pada Perusahaan DPD REI Sumatera Utara - Rahman Ali Nasution; Muhammad Akbar Al-Ghifari Barus; Muhammad Arif (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
Currently, the SLF is a requirement for evaluating the administrative and technical suitability of the building. The growth of industries has led to the government requiring the publication of SLF in order to legalize a business or structure, particularly those engaged in the sale of buildings or the provision of building amenities. In the company DPD REI SUMATERA NORTH, SLF (Certificate of Laik Function) is a phenomenon that this study aims to explore and explain. The author also emphasizes the effect of the worth and effectiveness of SLF's publication on the research locus. This study employed a case study approach to qualitative research as its methodology. Researchers seek for literature pertinent to research concerns as part of their data gathering procedures. from books, theses, journals, research essays, and research reports. The researchers in this study used Scopus, Google Scholar, and other sources to cite earlier journals. According to the study's findings, the issuing of the SLF (Laik Function Certificate) had a favorable effect on the worth and productivity of the business DPD REI SUMATERA NORTH. This offers convenience and a fulfilling employment so it can draw in investors and the general public to enhance marketing. The SLF's release is an urgent matter for a firm to address in order to raise quality and have a favorable effect on the economy and revenue.